The status of hard coral diversity at Christmas Island and Cocos (Keeling) Islands - Richard, Z.; Hobbs, Jean-Paul (Raffles Museum of Biodiversity Research, 2014)
Very little is known about the coral biodiversity in Australia’s remote Indian Ocean Territories; hence it is not possible to detect extinctions, depletions or to quantify changes in the coral fauna. Here we document the results of rapid visual assessment surveys of hard coral biodiversity at Christmas Island. This study provides a much-needed updated species list as well as a baseline dataset on coral community composition that will enable detection of future changes in the community. From this survey, a total of 145 species of scleractinian coral and five species of non-scleractinian coral (three hydrozoans and two octocorals) from 51 genera were recorded, including 28 range extensions. When combined with existing specimen-based records, the current estimate of hard coral species richness at Christmas Island is 169, and comparable to communities at other isolated Indian Ocean localities. In conjunction with the results of a previous study at neighbouring Cocos (Keeling) Islands, the total number of hard corals recorded from Australia’s Indian Ocean Territories is 197 species. The composition of the coral community is biogeographically unique and its long-term conservation is dependent on greater protection from local pollution impacts to safeguard resilience.